2021
DOI: 10.1080/19415257.2021.1901236
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Huber’s evaluation framework for teacher professional development programme

Abstract: This paper presents an enhanced evaluation framework for teacher professional development programmes, which is based on one originally proposed by Huber in 2011. This paper draws on a study on the Professional Up-skilling of English Language Teachers (ProELT) programme in Sabah (Borneo), Malaysia. The study adopted a mixed methods exploratory sequential design using a questionnaire survey, individual interviews and a focus group discussion. Based on the findings from the study, four new components have been ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…A study of Hubers et al (2020) highlight only two characteristics of andragogy in their study suggesting that when designing a course for adult learners, in their case, a teacher development program, educators should match between learning goals and the designed activities. Although a study shows that the application of six principles andragogy has enhanced English students' skills (Syamsuddin & Jimi, 2018), a study of Hiew and Murray (2021) find that six principles of andragogy were only partially implemented and the program did not completely address the learning needs and learning approaches of the adult learners. Besides, a study conducted in Saudi Arabia at Taif University revealed that students have different perspectives toward the characteristics of andragogy (Aljohani & Alajlan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A study of Hubers et al (2020) highlight only two characteristics of andragogy in their study suggesting that when designing a course for adult learners, in their case, a teacher development program, educators should match between learning goals and the designed activities. Although a study shows that the application of six principles andragogy has enhanced English students' skills (Syamsuddin & Jimi, 2018), a study of Hiew and Murray (2021) find that six principles of andragogy were only partially implemented and the program did not completely address the learning needs and learning approaches of the adult learners. Besides, a study conducted in Saudi Arabia at Taif University revealed that students have different perspectives toward the characteristics of andragogy (Aljohani & Alajlan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evaluation model by Huber (Huber, 2011), the highly influential Adult Learning Theory, first proposed by Knowles (1980) and further developed by him and subsequent researchers, is known as andragogy, which is defined as 'the arts and science of helping adults to learn' (Knowles, 1980) and the andragogical model by Knowles et al (2005) (Knowles et al, 2005) Additionally, this evaluation model provides guidance for program designers and providers to evaluate the program's impact by adjusting evaluation methods to align with the program's goals (Hiew & Murray, 2021).…”
Section: Model For Evaluating Professional Development Activities For...mentioning
confidence: 99%
“…Therefore, it can be seen that Wendy Hiew and Jill Murray's evaluation model is a comprehensive model with various factors. (Hiew & Murray, 2021). However, the application of any researcher's evaluation model depends on the specific evaluation purpose and conditions.…”
Section: Model For Evaluating Professional Development Activities For...mentioning
confidence: 99%
See 2 more Smart Citations